Advanced hydrogel strain sensors from non-aqueous resins via UV-cured 3D printing - Binbin Guo; Xiaoteng Chen; Hui Ying Yang; Jiaming Bai (Advanced Manufacturing)
Hydrogel-based strain sensors have attracted considerable interest in real-time healthcare and motion detection because of their remarkable flexibility, extensibility, and skin-like compatibility. To reduce the cost and accelerate the preparation of hydrogels, digital light processing (DLP) 3D printing technology presents a promising strategy. However, current photosensitive resin systems primarily use aqueous slurries, which slow down the 3D printing process due to high water content. Herein, we selected three non-aqueous resins for hydrogel preparation and adopted a two-step strategy involving UV curing through 3D printing followed by water spraying. We systematically investigated the curing kinetics and rheological properties of resins, as well as water absorption behavior, mechanical characteristics, and tensile-fracture mechanisms of the resulting hydrogels. Our findings established the poly (Nacryloylmorpholine) hydrogel as the reliable substrate material, NaCl aqueous solution was sprayed to endow the hydrogel with promising ionic conductivity and sensing properties. This work paves the way for the rapid fabrication of 3D printed ionically conductive hydrogels from non-aqueous resins.